2020
DOI: 10.21037/gs-20-641
|View full text |Cite
|
Sign up to set email alerts
|

The role of multimodal ultrasonic flow imaging in Thyroid Imaging Reporting and Data System (TI-RADS) 4 nodules

Abstract: Background: Color Doppler imaging (CDFI), contrast-enhanced ultrasound (CEUS), and superb microvascular imaging (SMI) are used to observe blood flow characteristics in Thyroid Imaging Reporting and Data System (TI-RADS) 4 nodules. The ability of these techniques to distinguish benign from malignant nodules was investigated.Methods: A total of 75 TI-RADS 4 nodules were examined using CDFI, SMI, and CEUS. The blood flow characteristics shown by the three methods were added to the current TI-RADS classification t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Hypo-enhancement on CEUS is considered the most precise predictor of malignancy for thyroid nodules with high sensitivity, specificity, and accuracy of 82%, 85%, and 84%, respectively ( 5 ). While iso-/hyper-enhancement on CEUS can suggest benignity ( 16 , 17 ). However, in our clinical practice, one-third of nodules with American College of Radiology’s Thyroid imaging reporting and data system (ACR TI-RADS) ( 18 ) category 4 and 5 on conventional US appear iso-/hyper-enhancement on CEUS (we defined as “non-hypovascular thyroid nodules”) that turn out to be malignant.…”
Section: Introductionmentioning
confidence: 99%
“…Hypo-enhancement on CEUS is considered the most precise predictor of malignancy for thyroid nodules with high sensitivity, specificity, and accuracy of 82%, 85%, and 84%, respectively ( 5 ). While iso-/hyper-enhancement on CEUS can suggest benignity ( 16 , 17 ). However, in our clinical practice, one-third of nodules with American College of Radiology’s Thyroid imaging reporting and data system (ACR TI-RADS) ( 18 ) category 4 and 5 on conventional US appear iso-/hyper-enhancement on CEUS (we defined as “non-hypovascular thyroid nodules”) that turn out to be malignant.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that malignant nodules had mainly hypo-enhancement [62][63][64][65][66], which can be due to fibrosis and neovascular damage by tumor cells, while benign nodules had hyper-enhancement or iso-enhancement, similar to normal tissue. Zang et al reported a higher sensitivity and lower specificity of CEUS + SMI in 75 suspicious nodules, compared with CEUS or SMI alone [67].…”
Section: Color Doppler Flow Imaging (Cdfi) Power Doppler Us and Superb Micro-vascular Imaging (Smi)mentioning
confidence: 99%
“…74 Zhang et al 75 found that the combination of TI-RADS and CEUS can significantly improve the diagnostic accuracy of thyroid nodules, especially TI-RADS 4 nodules. Zhang et al 68 studied the thyroid TI-RADS 4 nodules and found that SMI can better capture type II blood flow in benign nodules and type III blood flow in malignant nodules than CDFI. While CEU has the highest diagnostic value, the joint examination using SMI and CEU shows some advantages in sensitivity, although the overall accuracy is the same as that of CEU alone.…”
Section: Multimodal Ultrasoundmentioning
confidence: 99%
“…Huang et al 77 68 The results showed that the combination of twodimensional ultrasound TI-RADS and SMI or CEU could improve the diagnostic accuracy, and the diagnostic efficiency of the three combined diagnosis was further improved.…”
Section: Multimodal Ultrasoundmentioning
confidence: 99%